Princess on the brink - Cabot, Meg (New York HarperCollins, 2007)
Princess Mia's junior year in high school begins with a difficult course load, a crazy student council race, Grandmere's search for temporary lodging, and learning that her boyfriend is moving to Japan for a year, partly because she will not sleep with him
1
NEW, LITERATURE
Keywords: High schools -- Fiction; Humorous stories; Princesses -- Fiction; Schools -- Fiction; Sex -- Fiction; New York (N.Y.) -- Fiction